KAMPUNG NELAYAN BERKELANJUTAN DI KAMAL MUARA - Henry Yonanda; Rudy Trisno (Jurusan Arsitektur dan Perencanaan, 2019)
Millennials have been touted as the generation that will do something about global warming. Conversely, some social scientists studying generational differences have found evidence that younger generations are less likely to engage in civic matters like environmental activism. Lack of civic engagement among Millennials may reduce their likelihood of engaging in collective action on global warming. On the other hand, the world is drastically changing. Within the recent years, climate change has become a growing concern worldwide. The various modes of destruction imposed on the environment are targeted to be the catalyst to these changes. According to climate scientists, sea level rise is one of the most important impacts of global climate change. Fishermen as one of the professions that depend their life on the sea, is affected so much by this condition. This condition might destroy their houses on the coastal area. Urban Kampong in Jakarta as the most dense human settlements in urban area has become one of the main economic generator for a city. With all the contradict characteristics and forms, urban kampongs are the part of the city that cannot be separated from one to another. The existence of kampong has become the main embryo of the development of Jakarta. Jakarta is one of the biggest coastal city in the world. The coastline of this city has become the main economic generator for the coty and the nations. The existence of fishermen’s kampong in Jakarta has also become an essential program for the city, in order to fullfill the needs of fresh catch of sea products. Therefore, The project is aimed to create a sustainable and adaptive coastal kampong community, that has the resilience to the rising sea level. By concerning on the kampong’s behaviour, and doing research of the typological transformation of the kampong, the design is also expected to serve as an archetype fot the future development of endagered coastal settlements all across the country. several sustainable approach and behaviourial approach are also injected in this project to create a contextual design that would help the kampong to grow, and adapt to all the conditions, and situation in the future. AbstrakGenerasi milenial dianggap sebagai generasi yang akan melakukan perubahan nyata terkait dengan pemanasan global. Akan tetapi, beberapa studi pun menunjukan bukti bahwa generasi millenial justru memiliki kesadaran serta kepekaan yang tidak lebih tinggi dibandingkan dengan generas-generasi sebelumnya. Pada satu sisi, bumi kian melakukan perubahan yang begitu derastis. Berbagai macam kerusakan pun terjadi dalam berbagai jenis yang menjadi generator dari perubahan iklim yang drastis ini. Nelayan sebagai salah satu profesi yang menggantungkan nasibnya pada lautan, kian terganggu dengan kondisi ini. Hal ini menyebabkan kerusakan pada rumah-rumah di kawasan pesisir pantai. Kampung kota di Jakarta, sebagai permukiman terpadat di daerah urban menjadi salah satu kenerator utama pada suatu kota. Dengan segala karakteristiknya yang berbanding terbalik dengan perkotaan, kampung kota merupakan bagian yang tidak dapat dipisahkan dari suatu kota. Eksistensi suatu kampung telah menjadi embrio dari perkembangan kota Jakarta. Jakarta merupakan salah satu kota pesisir terbesar di dunia. Daerah pesisir dari kota ini telah menjadi generator ekonomi utama dari kota itu sendiri dan juga nasional. Keberadaan kampung nelayan di Jakarta pun menjadi salah satu program penting yang perlu mendapatkan perhatian. Maka dari itu, proyek ini bertujuan untuk menciptakan suatu komunitas kampung pesisir yang berkelanjutan, adaptif serta memiliki ketahanan terhadap kenaikan permukaan air laut yang terjadi. Metode perancangan pada proyek ini dibagi menjadi 2 bagian utama yaitu analisis mikro yang membahas mengenai tipe dan perilaku, serta analisis makro yang membahas proyek dari segi perancangan urban. Dengan menitik beratkan pada studi perilaku, dan melakukan riset mendalam terhadap transformasi tipologi yang terjadi pada kampung, desain ini diharapkan dapat menjadi suatu arketipe untuk pengembangan kampung di daerah pesisir di masa depan di seluruh Indonesia. Sehingga dapat disimpulkan, bahwa dengan adaptasi tipe, perilaku serta sistem berkelanjutan yang sesuai dan tepat, desain dari kampung nelayan berkelanjutan ini dapat menjadi suatu respon yang tepat dalam menjawab permasalahan yang terjadi di kampung-kampung pesisir.